Leaf Extract of Mirabilis jalapa L. Induced Defense of Tomato Plant (Lycopersicum esculentum Mill.) Against Cucumber Mosaic Virus (CMV) Infection - Dian Eka Kusumawati; Tutung Hadiastono; Luqman Qurata Aini (University of Brawijaya, 2012)
AbstractInfection of Cucumber Mosaic Virus (CMV) could reduce the tomato production up to 50%depending on the age of the plant during infection and tomato varieties. Until now the controlefforts against CMV infection have been made, but no consistent effective method was available.Recently, new approach by increasing the plant health to defense against plant disease wasincreased. It can be stimulated by inoculation of microbes associated with roots or by application of plant extract such as Mirabilis jalapa. In this study, the effect of M. jalapa leaf extract in differentconcentration to develop control against CMV infection in tomato plants was conducted. The results showed that the application of M. jalapa leaf extract could inhibit the development of CMV diseasein tomato plants. The higher the concentration of M. jalapa leaf extract applied on tomato plant, thelower disease incidence as well as the longer incubation period of CMV disease in tomato plants.The applications of M. jalapa leaf extract elevated the activity of peroxidase and catalase enzymes.Thus, the inhibition of CMV disease development in tomato plant by application of M. jalapa leafextract may related to the induction of peroxidase and catalase activity in tomato plants.Keywords: M. jalapa, CMV, plant defense, leaf extract, peroxidase, catalase